Letter frequency analysis of proprietary prescription drug names in the United States: Minding the Zs and Qs - Ron Carico, Jr; Keaton Kaplan; Kyler Gator Hazelett; Megan Dillon; Kelly Melvin (Elsevier, 2022)
Background: Proprietary or brand names of prescription drugs are generally with letters that are unusual in common English. There is little academic research exploring if this perception is true, despite the fact that manufacturers pay millions of dollars to research and develop drug names that conform to regulatory standards while remaining marketable. Objectives: To assess the extent to which letters used in prescription drug names may deviate from common English and to test if prescription drug names show measurable trends in letter frequency over time. Methods: The names of all prescription drugs approved in the United States between 1985 and 2020 were downloaded. Duplicates were removed and products without a proprietary name were excluded. Letter frequency analyses were then conducted on all letters in these names as an aggregate and year-over-year. Letter frequencies were compared to a validated academic reference, a corpus derived from all Google Books data, and the scoring system from the board game Scrabble. Results: Regardless of the comparator, prescription drug names use letters that are not common in typical English. Letters A (11.96% of all observed letters), V (3.08%), X (2.31%), and Z (1.91%) are all overrepresented in prescription drug names, while E (10.23%), H (0.90%), T (6.30%), and S (4.21%) are underrepresented. The letters C and N are becoming less common over time (frequency decrease of 0.10 percentage points and 0.12 percentage points per year, respectively), while V, Y, and Z are becoming more common (frequency increases of 0.61 to 0.86 percentage points per year). Conclusions: Proprietary prescription names use letters that are unlike words used in everyday American English, and there are measureable trends in letter selection. It remains to be seen how drug manufacturers will cope with an increasingly-narrow naming space as more products continue to be approved over time.